La disputa por el “cambio de paradigma” en Luhmann, Latour y Habermas - Pignouli Ocampo, Sergio (El Colegio de México, 2015)
This paper thematizes the performative components proposed by Luhmann’s General Social Systems Theory, Latour’s Actor-Network Theory and Habermas’s Communicative Action Theory which have the purpose to generate a Paradigm Shift in Sociology. Our hypothesis is that those performative components have points of divergence, but also of convergence. The latter are observed in the programmatical strategies of differentiation and articulation against the “crisis of Sociology” in the disciplinary context of Eighties and Nineties.